Porcine Invariant Natural Killer T Cells: Functional Profiling and Dynamics in Steady State and Viral Infections - Schäfer, Alexander; Hühr, Jane; Schwaiger, Theresa; Dorhoi, Anca; Mettenleiter, Thomas C.; Blome, Sandra; Schröder, Charlotte; Blohm, Ulrike (Frontiers in Immunology, 2019)
Pigs are important livestock and comprehensive understanding of their immune responses in infections is critical to improve vaccines and therapies. Moreover, similarities between human and swine physiology suggest that pigs are a superior animal model for immunological studies. However, paucity of experimental tools for a systematic analysis of the immune responses in pigs represent a major disadvantage. To evaluate the pig as a biomedical model and additionally expand the knowledge of rare immune cell populations in swine, we established a multicolor flow cytometry analysis platform of surface marker expression and cellular responses for porcine invariant Natural Killer T cells (iNKT). In humans, iNKT cells are among the first line defenders in various tissues, respond to CD1d-restricted antigens and become rapidly activated. Naïve porcine iNKT cells were CD3+/CD4–/CD8+ or CD3+/CD4–/CD8– and displayed an effector- or memory-like phenotype (CD25+/ICOS+/CD5hi/CD45RA–/CCR7±/CD27+). Based on their expression of the transcription factors T bet and the iNKT cell-specific promyelocytic leukemia zinc finger protein (PLZF), porcine iNKT cells were differentiated into functional subsets. Analogous to human iNKT cells, in vitro stimulation of porcine leukocytes with the CD1d ligand -galactosylceramide resulted in rapid iNKT cell proliferation, evidenced by an increase in frequency and Ki-67 expression. Moreover, this approach revealed CD25, CD5, ICOS, and the major histocompatibility complex class II (MHC II) as activation markers on porcine iNKT cells. Activated iNKT cells also expressed interferon-γ, upregulated perforin expression and displayed degranulation. In steady state, iNKT cell frequency was highest in newborn piglets and decreased with age. Upon infection with two viruses of high relevance to swine and humans, iNKT cells expanded. Animals infected with African swine fever virus displayed an increase of iNKT cell frequency in peripheral blood, regional lymph nodes and lungs. During Influenza A virus infection, iNKT cell percentage increased in blood, lung lymph nodes and broncho-alveolar lavage. Our in-depth characterization of porcine iNKT cells contributes to a better understanding of porcine immune responses, thereby facilitating the design of innovative interventions against infectious diseases. Moreover, we provide new evidence that endorses the suitability of the pig as a biomedical model for iNKT cell research.